Kejujuran Berteologi Kontekstualisasi: Teologi Lokal Gereja Kristen Injili Indonesia dalam Religi Orang Rimba - Heri Victor Ambarita; Fernando Tambunan (Sekolah Tinggi Teologi Baptis Medan, 2022)
Examine existing Contextual Theology ideas and thoughts regarding the theological honesty of the Indonesian Evangelical Christian Church in its Evangelical Mission with religion; kinship system; and the values of the nomadic life of the Orang Rimba (Suku Anak Dalam) along the interior of the Bukit Dua Belas National Park forest, Jambi province and the implementation of contextualization of Christian faith in the midst of the local Orang Rimba congregation. Methods: Qualitative research with Grounded Theory approach in compiling this article is to find the relationship between the preaching of the gospel that is preached from time to time so that it can reach the Suku Anak Dalam; how the faith and teachings of Christianity are consciously understood by them as a real manifestation of the task of the Great Commission (Matthew 28:18-20); and the implications of the contextualization of the down-to-earth Christian faith. encourage them to be more enthusiastic in producing various local biblical theologies; relevant to the culture, belief system, pattern of social life, culture and language of neglected and isolated tribes in Indonesia such as Orang Rimba (SAD). so it was found that the Anak Dalam tribe had believed through the Indonesian Evangelical Christian Church.Keywords: Honesty, Contextualization, Theology, Evangelical AbstrakMeninjau kembali gagasan dan pemikiran Teologi Kontekstual yang ada terhadap kejujuran berteologi Gereja Kristen Injili Indonesia dalam Misi Pekabaran Injil-Nya dengan religi; sistem kekerabatan; dan nilai-nilai kehidupan orang Rimba (Suku Anak Dalam) yang nomaden di sepanjang pedalaman hutan Taman Nasional Bukit Dua Belas, provinsi Jambi serta implementasi kontekstualisasi iman Kristen di tengah-tengah jemaat-jemaat lokal orang Rimba. Metode: Penelitian kualitatif dengan pendekatan Grounded Theory dalam menyusun artikel ini adalah guna menemukan relasi antara Pemberitaan Injil yang telah diberitakan dari masa ke masa hingga dapat menjangkau Suku Anak Dalam; bagaimana iman dan pengajaran kekristenan secara sadar dipahami oleh mereka sebagai wujud nyata dari tugas Amanat Agung (Matius 28:18-20); serta implikasi kontekstualisasi iman Kristen yang membumi. mendorong mereka supaya semakin bersemangat menghasilkan berbagai teologi lokal yang Alkitabiah; relevan dengan budaya, sistem kepercayaan, pola kehidupan sosial, budaya maupun bahasa dari suku-suku terabaikan dan terisolir di Indonesia seperti orang Rimba (SAD). sehingga ditemukan bahwa Suku Anak Dalam yang telah percaya melalui Gereja Kristen Injili Indonesia.Kata Kunci: kejujuran, kontekstualisasi, teologi, injil